Implementasi Program Waqaf Tunai dalam Pengentasan Kemiskinan di Indonesia - laila, resa; Happy Novasila Maharani; Dede Nurohman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cash waqf is a philanthropic concept that aims to collect funds from the community through donations which are then invested in building social, educational, health and economic infrastructure. This research aims to analyze the implementation of the cash waqf program in overcoming poverty in Indonesia. The research method used is literature study and analysis of secondary data related to the implementation of the cash waqf program in Indonesia, as well as its impact on improving community welfare. The research results show that the implementation of the cash waqf program has made a positive contribution in reducing poverty levels in Indonesia. These programs include the establishment of education centers, development of health infrastructure, business capital assistance for underprivileged communities, and local economic empowerment programs. However, there are still challenges in optimizing and managing waqf funds as well as developing sustainable programs to increase their wider impact. In conclusion, the implementation of the cash waqf program has great potential in overcoming poverty in Indonesia, but good coordination is needed between the government, sharia financial institutions and the community to ensure the sustainability and effectiveness of the program. This research provides useful insights for stakeholders in developing strategies and policies that support the growth of cash waqf as an effective instrument in alleviating poverty.